Searching for Dark Particles with Quantum Optics - Estrada, J. (2021)
We propose a way to use optical tools from quantum imaging and quantum communication to search for physics beyond the standard model. Spontaneous parametric down-conversion (SPDC) is a commonly used source of entangled photons in which pump photons convert to a signal-idler pair. We propose to search for "dark-SPDC"(dSPDC) events in which a new dark-sector particle replaces the idler. Though it does not interact, the presence of a dark particle can be inferred by the properties of the signal photon. Examples of dark states include axionlike particles and dark photons. We show that the presence of an optical medium opens the phase space of the down-conversion process, or decay, which would be forbidden in a vacuum. Search schemes are proposed that employ optical imaging and/or spectroscopy of the signal photons. The signal rates in our proposal scales with the second power of the small coupling to new physics, as opposed to light-shining-through-wall experiments, the signal of which scales with coupling to the fourth power. We analyze the characteristics of the optical media needed to enhance dSPDC and estimate the rate.